Sub-acute toxicity of lantadenes isolated from Lantana camara leaves in guinea pig animal model. (November 2015) - Parimoo, Haroon; Sharma, Rinku; Patil, Rajendra; Patial, Vikram
Abstract The sub-acute toxicity of lantadenes isolated fromLantana camara leaves was studied in guinea pig laboratory animal model. A total of 20 guinea pigs of either sex were divided into five groups. Group I served as control, while groups II, III, IV, and V were orally administered lantadenes at the dose rate of 100, 50, 25, and 12.5 mg/kg body weight (bw), respectively for 28 days. The levels of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, acid phosphatase, total bilirubin, blood urea nitrogen, and creatinine were estimated in serum. The effect of lantadenes on lipid peroxidation, superoxide dismutase, reduced glutathione, and catalase was monitored in liver homogenate. The lantadenes at the dose rate of 25 mg/kg bw in animals of group IV did not result in mortality, produced gross and histopathological changes characteristic of sub-acute toxicity in liver and kidneys, and resulted in the highest levels of serum liver marker enzymes. Elevated lipid peroxidation levels and decreased levels of superoxide dismutase and catalase in group IV indicated free-radical-induced damage by lantadenes. It was concluded that lantadenes produced a dose-dependent toxicity and the dose level of 25 mg/kg bw was the sub-acute toxic dose which induced significant fibrosis and necrosis in liver of guinea pigs. To the best of our knowledge, this is the first report on the study of sub-acute toxicity of lantadenes in guinea pig animal model which mimic the actual livestock lantana toxicity cases in field conditions.